ANALISIS PENULISAN KATA DEPAN DALAM TUGAS MENULIS WACANA ESKPOSISI KELAS X MIPA 1 SMA NEGERI 3 KOTA JAMBI - Supriyati Supriyati; Fajar Ahmad (Universitas Batanghari, 2022)
The purpose of this research is to describe the writing prepositions di, ke, and dari from the the exposition writing task of class X MIPA students of SMA Negeri 3 Jambi City academic year 2019/2020. This research is included in the type of qualitative descriptive research. Qualitative descriptive research is intended to investigate circumstances, conditions, or other things, the results of which are presented in the form of research reports in the form of data. The data of this research are findings in the form of quotations in the exposition assignment of class X MIPA 1 students of SMAN 3 Jambi City. The results of this study are the use of prepositions di, ke, and dari in the exposition task of class X MIPA 1 students of SMAN 3 Jambi City. Based on the results of this study, it can be concluded that the analysis of writing prepositions (di, ke, and dari) in the task of the exposition of class X MIPA students of SMA Negeri 3 Jambi City for the academic year 2019/2020. The preface is found in twenty-two citations. The preposition found in the text is nineteen quotes. The preposition of dari is found twenty-two citations.